2014
DOI: 10.25120/qar.17.2014.229
|View full text |Cite
|
Sign up to set email alerts
|

The significance of Levallois and discoidal technology in the Arcadia Valley, south central Queensland

Abstract: <p>An analysis of stone artefacts from the Arcadia Valley in south central Queensland is used to develop a core reduction sequence model for the region. During the initial construction of this model, core types are identified that reflect phases or end points in reduction trajectories. The model shows that core reduction methods employed in the Arcadia Valley during the mid-to-late Holocene included Levallois, discoidal, prismatic and burin blade core methods, along with less formal reduction strategies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…As regards the presence of the Levallois technique in lithic production in Australia, it is necessary to refer to the publication of Grant. W. G Cochrane (2014). Cochrane analysed a surface-collected lithic assemblage of a total of 5,095 artefacts from the Arcadia Valley (South Central Queensland).…”
Section: The Technologymentioning
confidence: 99%
“…As regards the presence of the Levallois technique in lithic production in Australia, it is necessary to refer to the publication of Grant. W. G Cochrane (2014). Cochrane analysed a surface-collected lithic assemblage of a total of 5,095 artefacts from the Arcadia Valley (South Central Queensland).…”
Section: The Technologymentioning
confidence: 99%
“…First, he demonstrated that knapping strategies (e.g. flaking patterns) changed during the reduction process (see also Wallace and Shea, 2006;Cochrane, 2014), emphasizing that "The morphology viewed on any given core […] will represent only the last actions that were performed on it" (Dibble, 1995, p. 102). Second, different cores in an assemblage may be discarded at different stages in the reduction sequence (e.g.…”
Section: A Cores-only Approach To Reconstructing Reduction Strategiesmentioning
confidence: 99%